PENGARUH KOMPETENSI TENAGA ADMINISTRASI TERHADAP PELAYANAN ADMINISTRASI PESERTA DIDIK DI UPT SMPN 2 AJANGALE KABUPATEN BONE - Mita Permatasari; Besse Herlina; Muh. Asrul; Sumarni; Jusman; Emi; Angga Alhamdani; Evita Lestari (Universitas Al-Qolam Malang, 2024)
This study aims to determine the effect of administrative staff competence on student administrative services at UPT SMPN 2 Ajangale, Bone Regency using a quantitative approach. The population in this study were students at UPT SMPN 2 Ajangale, Bone Regency, totaling 190 students. While the number of samples in this study was carried out using Slovin's opinion, from the calculation results obtained a sample size of 66 students. Data collection was carried out in two ways, namely questionnaires (questionnaires) and documentation. The data analysis technique uses percentage analysis, Pearson product moment correlation coefficient analysis, and determination coefficient analysis. The results of research and data analysis show that, (1) the competence of administrative staff at UPT SMPN 2 Ajangale Bone Regency received a very good assessment, with a percentage of 80%, (2) administrative services for students at SMPN 2 Ajangale Bone Regency were also in the very good category, with a percentage of 79%, (3) there is an effect of administrative staff competence of 60.5% on student administrative services, while the remaining 39.5% is influenced by other aspects not examined in this study. From these results, it shows that the higher the competence of administrative staff at UPT SMPN 2 Ajangale, Bone Regency, the more administrative services for students will increase.